Pre-diagnostic blood biomarkers for adult glioma - Andrews, Lily J.; Davies, Philippa; Herbert, Christopher; Kurian, Kathreena M. (Frontiers in Oncology, 2023)
Glioma is one of the most common malignant primary brain tumours in adults, of which, glioblastoma is the most frequent and malignant entity. Glioma is often diagnosed at a later stage of disease progression, which means it is associated with significant mortality and morbidity. Therefore, there is a need for earlier diagnosis of these tumours, which would require sensitive and specific biomarkers. These biomarkers could better predict glioma onset to improve diagnosis and therapeutic options for patients. While liquid biopsies could provide a cheap and non-invasive test to improve the earlier detection of glioma, there is little known on pre-diagnostic biomarkers which predate disease detection. In this review, we examine the evidence in the literature for pre-diagnostic biomarkers in glioma, including metabolomics and proteomics. We also consider the limitations of these approaches and future research directions of pre-diagnostic biomarkers for glioma.